Analisis Determinan Return Saham pada Perusahaan Manufaktur - Risma Nurhapsari (Jurnal Ilmiah Aset, 2023)
Manufacturing stocks are the most sensitive sector to changes in macroeconomic conditions and have different stock return volatility. Return is the rate of return obtained from the investment. The purpose of this study was to analyze the different effects of macroeconomic indicators such as inflation, interest rates and the IDR/USD exchange rate on stock returns in the manufacturing sector. Another factor that is thought to influence stock returns is the debt to equity ratio. This research is a quantitative research with the object of research on manufacturing companies listed on the IDX. The sample used is manufacturing companies that meet the criteria, so that obtained 76 companies during the years 2007-2009. Research data obtained by using documentation techniques. From the data obtained and analyzed using the SPSS 17.00 program, with multiple linear regression analysis tools. The results of this study indicate the results of 2 independent variabels, namely interest in the exchange rate and foreign exchange rates have a significant effect on stock returns with a negatif coefficient indicated by the significance level of 0.000 and 0.001. While the other 2 independent variabels, namely inflation and DER have no significant effect on stock returns, this is indicated by a significance level of 0.527 and 0.63.